The Ups and Downs of the Nigerian Society: A Satirical View on Socio-political Matters in Chimamanda Ngozi Adichie’s Purple Hibiscus (2004) and Sefi Atta’s a Bit of Difference (2013) - Babacar Diakhate (Budapest International Research and Critics University, 2019)
This paper aims to show the objectivity of Nigerian writers by portraying the ups and downs of their society. Indeed, in Sefi Atta’s a Bit of Difference and Chimamanda Ngozi Adichie’s Purple Hibiscus, the authors have done a diagnosis without complaisance of the bottlenecks that impede Nigeria from moving forwards. It also demonstrates that feminist activism can challenge a political military power. It finally displays that violence at universities; social injustice, corruption and mediocrity are the evils that characterized the Nigerian society.